Intrinsic red polyimide nanoparticles and preparation method thereof, electrophoretic ink

CN122897991APending Publication Date: 2026-10-13JIANGHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611154375.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

粒子色彩来源依赖物理共混:传统彩色电泳粒子大多通过物理吸附或包覆方式引入着色剂,着色剂容易脱落、迁移,导致颜色不稳定,长期使用后色彩褪色、饱和度和对比度下降,影响显示质量和器件寿命

Benefits of technology

1.本发明以PTCDA(3,4,9,10-苝四甲酸二酐)为红色生色前驱体,通过缩聚反应将其苝核以共价键方式嵌入聚酰亚胺分子主链。PTCDA的苝核具有大π共轭结构,在400~550nm蓝绿光区产生强烈吸收,依据补色原理呈现鲜艳红色。与物理吸附或包覆颜料/染料的方式相比,本发明通过C-N共价键将生色团锚定在每条分子链上,实现了分子级别的均匀着色,从根本上杜绝了颜料团聚、染料迁移及热分解等问题,颜色均匀性、耐热性和长期稳定性显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897991A_ABST
    Figure CN122897991A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of electrophoretic display, and particularly relates to a kind of intrinsic red polyimide nanoparticles and preparation method thereof, electrophoretic ink.A kind of intrinsic red polyimide nanoparticles preparation method, comprising: PTCDA, 6FDA and TFMB are dissolved in solvent, and red modified PAA-containing mixed solution is obtained by reaction;Red modified PAA micro-particle is obtained by dropping red modified PAA-containing mixed solution into water and centrifuging, and red modified PAA solution is obtained by dissolving in solvent;Red modified PAA solution is used as dispersion phase, oil solvent containing surfactant is used as continuous phase, emulsion droplet is generated by using microfluidic chip, and intrinsic red polyimide nanoparticles are obtained after solvent replacement and thermal imidization of emulsion droplet.The present application fundamentally eliminates the problems such as pigment aggregation, dye migration and thermal decomposition, and the color uniformity, heat resistance and long-term stability are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrophoretic display technology, specifically to an intrinsic red polyimide nanoparticle, its preparation method, and an electrophoretic ink. Background Technology

[0002] Electrophoretic display (EPD) technology displays images based on the migration of charged particles in an electric field. It offers advantages such as low power consumption, comfortable reading, and bistable operation, making it the mainstream technology for electronic paper. With monochrome electrophoretic displays already commercialized, developing color electrophoretic displays is a current research hotspot and a key direction for industrial development. One of the key technologies for achieving color electrophoretic displays lies in preparing electrophoretic display particles with a high charge-to-mass ratio, good dispersion stability, and vibrant colors.

[0003] Currently, the preparation of colored electrophoretic particles mainly involves surface coating or modification of organic or inorganic pigments. However, organic pigment particles suffer from drawbacks such as easy aggregation, low zeta potential, and poor dispersion stability in nonpolar media; while inorganic pigment particles have high density and fast sedimentation rate, affecting the response speed and stability of electrophoretic displays. The existing technology has the following problems: Particle color source relies on physical blending: Traditional color electrophoretic particles mostly introduce colorants through physical adsorption or coating. Colorants are prone to falling off and migrating, resulting in unstable colors. After long-term use, colors fade, saturation and contrast decrease, affecting display quality and device lifespan. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing a method for preparing intrinsic red polyimide nanoparticles, comprising: PTCDA and 6FDA were dissolved in a solvent to obtain a dianhydride solution. TFMB was dissolved in a solvent to obtain a diamine solution. The dianhydride solution and the diamine solution were mixed and reacted to obtain a mixed solution containing red modified PAA. A mixed solution containing red modified PAA was added dropwise to water and then centrifuged to obtain red modified PAA microparticles. The red modified PAA microparticles were then dissolved in a solvent to obtain a red modified PAA solution. A red modified PAA solution was used as the dispersed phase, and an oily solvent containing a surfactant was used as the continuous phase. The solution was passed through a microfluidic chip to generate emulsion droplets. The emulsion droplets were then dropped into water and centrifuged to obtain red modified PAA nanoparticles. The red modified PAA nanoparticles were subjected to step-heat thermal imidization to obtain intrinsic red polyimide nanoparticles. In particular, the solvent in the red modified PAA solution is immiscible with the oily solvent, and the oily solvent is a poor solvent for the red modified PAA.

[0005] Furthermore, the red modified PAA solution contains 5-7 wt% red modified PAA, and the oily solvent containing surfactant contains 1-3 wt% surfactant.

[0006] Furthermore, the total amount of PTCDA and 6FDA is in a 1:1 ratio with the amount of TFMB.

[0007] Furthermore, when the mixed solution containing red modified PAA is dropped into water, the red modified PAA molecular chains rapidly collapse and aggregate in the desolvated environment after the solvent is replaced by water, forming red modified PAA microparticles.

[0008] Furthermore, when the emulsion droplets are dropped into water again, the oily solvent separates into layers with the water. The solvent in the red modified PAA solution diffuses out from the emulsion droplets and is extracted and replaced by water. The red modified PAA molecular chains collapse and aggregate in the desolvated environment to form red modified PAA nanoparticles.

[0009] Furthermore, the specific method for the stepwise heating thermal imidization is as follows: under vacuum conditions, the temperature is gradually increased in stages of 100℃, 150℃, 200℃, 250℃, and 300℃, and each temperature stage is held for 1 hour.

[0010] Furthermore, the reaction between the dianhydride solution and the diamine solution is a condensation reaction. PTCDA and 6FDA randomly undergo condensation reaction with TFMB to obtain red modified PAA. The perylene core of PTCDA is covalently embedded in the main chain of red modified PAA as a red chromophore.

[0011] An intrinsic red polyimide nanoparticle prepared according to the above preparation method.

[0012] An electrophoretic ink comprising the aforementioned intrinsic red polyimide nanoparticles.

[0013] The beneficial effects of this invention are as follows: 1. This invention uses PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) as a red chromophore precursor, and its perylene core is covalently embedded into the polyimide molecular backbone through a condensation reaction. The perylene core of PTCDA has a large π-conjugated structure, exhibiting strong absorption in the 400-550 nm blue-green light region, and presents a bright red color according to the complementary color principle. Compared with physical adsorption or pigment / dye coating methods, this invention anchors the chromophore to each molecular chain through CN covalent bonds, achieving uniform coloring at the molecular level. This fundamentally eliminates problems such as pigment aggregation, dye migration, and thermal decomposition, significantly improving color uniformity, heat resistance, and long-term stability.

[0014] 2. This invention employs microfluidic emulsion droplet technology, utilizing the shearing action between the continuous phase and the dispersed phase in a flow-focusing chip to generate monodisperse emulsion droplets. By precisely controlling the channel size (100 μm) and the two-phase flow rate ratio (2 mL / h for the dispersed phase and 20 mL / h for the continuous phase), the emulsion droplet size is uniform and controllable. In the subsequent solvent displacement process, red modified PAA nanoparticles are obtained, which are then subjected to step-heat thermal imidization to finally obtain regularly spherical red polyimide nanoparticles. Figure 1 , Figure 2 As shown, the product has a narrow particle size distribution and regular morphology, which significantly improves the contrast and response consistency of electrophoretic display compared with traditional grinding or emulsion methods.

[0015] 3. The trifluoromethyl group in TFMB and the hexafluoroisopropyl group in 6FDA impart a non-coplanar conformation to the molecular chain, disrupting the regular stacking of chain segments. This ensures both the good solubility of the precursor in DMAc and the high bond energy of the CF bond, guaranteeing the thermal stability of the material. In the examples, the molar proportion of PTCDA is 10%~50%. After the perylene core is randomly embedded in the main chain, the chain segments still maintain sufficient flexibility due to the steric hindrance effect of the TFMB / 6FDA backbone. Therefore, the introduction of the red chromophore imparts an intrinsic red color to the material without significantly impairing the original excellent heat resistance and mechanical properties of polyimide.

[0016] Figure 1 This is a scanning electron microscope image of Example 1. Attached Figure Description

[0017] Figure 1 This is a scanning electron microscope image of Example 1.

[0018] Figure 2 This is a particle size distribution diagram of Example 1.

[0019] Figure 3 This is the FTIR infrared spectrum of Example 2.

[0020] Figure 4 The images show the Zeta potential histograms for Examples 1, 2, and 3. Detailed Implementation

[0021] Unless otherwise specified, all raw materials used below are commercially available products, and all methods used below are conventional methods in this field.

[0022] A method for preparing intrinsically red polyimide nanoparticles, comprising: PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) and 6FDA (4,4'-(hexafluoroisopropylidene)dianhydride) were dissolved in a solvent to obtain a dianhydride solution. TFMB (2,2'-bis(trifluoromethyl)benzidine) was dissolved in a solvent to obtain a diamine solution. The dianhydride solution and the diamine solution were mixed and reacted to obtain a mixed solution containing red modified PAA. A mixed solution containing red modified PAA was added dropwise to water and then centrifuged to obtain red modified PAA (polyamic acid) microparticles. The red modified PAA microparticles were dissolved in a solvent to obtain a red modified PAA solution. A red modified PAA solution was used as the dispersed phase, and an oily solvent containing a surfactant was used as the continuous phase. The solution was passed through a microfluidic chip to generate emulsion droplets. The emulsion droplets were then dropped into water and centrifuged to obtain red modified PAA nanoparticles. The red modified PAA nanoparticles were then subjected to step-heat thermal imidization to obtain intrinsic red polyimide nanoparticles. In particular, the solvent in the red modified PAA solution is immiscible with the oily solvent, and the oily solvent is a poor solvent for the red modified PAA.

[0023] Solvents include, but are not limited to, one or more of N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), m-cresol, and N,N-dimethylformamide (DMF).

[0024] Surfactants include, but are not limited to, one or more of Span 80, Span 85, Tween 20, Tween 60, Tween 80, and Tween 85.

[0025] Oily solvents include, but are not limited to, silicone oil, mineral oil, Isopar series solvents (such as Isopar G, Isopar H), dodecane, and one or more of tetrachloroethylene.

[0026] In one specific implementation, the red modified PAA solution contains 5-7 wt% red modified PAA, and the oily solvent containing surfactant contains 1-3 wt% surfactant. The surfactant is used to reduce interfacial tension and prevent emulsion droplet aggregation, ensuring the stability and monodispersity of microfluidic emulsion droplet formation, while also taking into account the spherical integrity of the particles after curing.

[0027] In one specific implementation, the total amount of PTCDA and 6FDA is in a 1:1 ratio with the amount of TFMB. The formation of polyamic acid is a stepwise polycondensation reaction; only when the functional groups of the dianhydrides (PTCDA and 6FDA) react in equal molar amounts with the diamine (TFMB) can the molecular chain continue to grow. If any monomer is in excess, the excess functional groups will cap the molecules, resulting in a lower molecular weight, a less dense network after subsequent imidization, and decreased mechanical properties and heat resistance.

[0028] In one specific implementation, when the mixed solution containing red modified PAA is dropped into water, the red modified PAA molecular chains rapidly collapse and aggregate in the solvent-free environment after the solvent is replaced by water, forming red modified PAA microparticles. Water titration causes the red modified PAA to precipitate from the solution, while centrifugation and washing remove unreacted PTCDA, 6FDA, TFMB, and byproducts, preventing these impurities from interfering with the interfacial stability of the emulsion droplets during subsequent microfluidic processes. The mass fraction and viscosity of the mixed solution containing red modified PAA after direct polymerization are difficult to control precisely, while the formation of microfluidic emulsion droplets is extremely sensitive to the rheological properties of the dispersed phase. Through drying and redissolving, the concentration of red modified PAA can be precisely controlled to the window most suitable for the shearing of the microfluidic emulsion droplets.

[0029] In one specific implementation, when the emulsion droplets are dropped into water again, the oily solvent and water separate into layers. The solvent in the red modified PAA solution diffuses out from the emulsion droplets and is extracted and replaced by water. The red modified PAA molecular chains collapse and aggregate in the desolvated environment to form red modified PAA nanoparticles.

[0030] In one specific implementation, the microfluidic chip has a channel size of 50–500 μm, a dispersed phase flow rate of 0.5–10 mL / h, and a continuous phase flow rate of 5–100 mL / h. The channel size, dispersed phase flow rate, and continuous phase flow rate together determine the two dimensionless parameters, capillary number and flow rate ratio, which are the dominant factors in the emulsion droplet formation mode and size. By synergistically controlling these three parameters, emulsion droplet formation can be stabilized in a trickling mode, resulting in emulsion droplets with uniform particle size and regular morphology. Subsequent solvent displacement curing and thermal imidization transform these droplets into intrinsically red polyimide nanoparticles with highly controllable size and excellent monodispersity, thereby ensuring the contrast, response consistency, and long-term stability of the electrophoretic display device.

[0031] In one specific implementation, the reaction between the dianhydride solution and the diamine solution is a polycondensation reaction. PTCDA and 6FDA are randomly reacted with TFMB to produce red modified PAA. The perylene core of PTCDA is covalently embedded in the main chain of the red modified PAA as a red chromogenic unit.

[0032] The lone pair of electrons on the nitrogen atom of the aromatic primary amine (-NH2) of TFMB attacks the carbonyl carbon of the anhydride ring of PTCDA or 6FDA. The anhydride ring has high ring strain and is far more nucleophilic than ordinary amides, thus allowing for rapid ring-opening at 0°C. After ring-opening, a carboxylic acid (-COOH) and an amide bond (-CONH-) are formed, resulting in an ammonic acid structure. This structure is a precursor to polyimide and is not yet closed. As TFMB continues to attack PTCDA or 6FDA, the molecular chain gradually grows, forming a linear polymeric polyamic acid (PAA). Due to the random reaction of PTCDA and 6FDA with TFMB, the perylene core of PTCDA is randomly covalently inserted into the main chain.

[0033] The red color does not originate from PAA itself, as pure PAA is colorless. Instead, it comes from the perylene core's large conjugated structure introduced by PTCDA. The perylene core of PTCDA has a strong absorption band in the 400-550 nm region (corresponding to the blue-green light region). According to the principle of complementary colors, after the material absorbs blue-green light, the remaining red-orange light dominates in the transmitted / reflected light, thus appearing red to deep red to the naked eye. When PTCDA participates in condensation polymerization, the anhydride rings on both sides of the perylene core are opened and connected to the benzene rings of TFMB, but the fused-ring conjugated skeleton of the perylene core itself is completely preserved. The perylene core, as a red chromophore, is covalently anchored to the main chain. Due to the covalent bond, the perylene core is uniformly dispersed in the polymer, does not migrate, and does not agglomerate, exhibiting a uniform and stable intrinsic red color. If it were a physically mixed red pigment, the pigment particles would scatter light and easily agglomerate, resulting in uneven color. Here, the perylene core is chemically bonded to each molecular chain, achieving uniform coloring at the molecular level.

[0034] As a specific implementation method, the stepwise heating thermal imidization is carried out under vacuum conditions, with temperatures progressively increased to 100℃, 150℃, 200℃, 250℃, and 300℃, and each temperature stage held for 1 hour. The spherical structure of the red modified PAA nanoparticles obtained after solvent displacement curing possesses sufficient mechanical strength to resist thermal stress and internal vapor pressure during the stepwise heating process, preventing particle adhesion, fusion, or cracking. For nanoscale particles, sudden heating can easily lead to rapid vaporization of internal moisture, causing particle expansion, cracking, or deformation. Stepwise holding ensures a gentle and controllable dehydration process, thereby locking in the spherical morphology imparted by microfluidics. During curing, the surfactant in the oily continuous phase remains adsorbed on the particle surface, acting as a steric hindrance in the early stages of thermal imidization, preventing thermal adhesion between particles. At 100-150℃, residual solvent and adsorbed water are removed, and the particles are initially shaped. At 150-200℃, the amic acid groups of the red modified PAA begin to undergo intramolecular dehydration and ring closure. The -COOH reacts with the ortho-NH-CO- to form a five-membered cyclic imide structure (-CO-N-CO-), releasing water molecules. At 250-300℃, imidization tends to be complete, and the molecular chain segments rearrange to form a dense three-dimensional network structure.

[0035] The present invention also provides an intrinsic red polyimide nanoparticle prepared according to the above preparation method.

[0036] The present invention also provides an electrophoretic ink comprising the above-described intrinsic red polyimide nanoparticles.

[0037] To demonstrate the beneficial effects of the present invention, the following embodiments and comparative examples are provided.

[0038] Example 1 The preparation of intrinsic red polyimide nanoparticles with a PTCDA molar ratio of 10% is detailed below: (1) Raw material ratio. The total molar ratio of dianhydride monomer to diamine monomer is fixed at n(6FDA+PTCDA):n(TFMB)=1:1, the solid content of the polymerization system is constant at 6wt%, and the total reaction system volume is 50mL. The molar percentage of PTCDA in the mixed dianhydride is 10%. Based on a solid content of 6wt% and a total reaction system volume of approximately 50mL, weigh out 0.157g of PTCDA, 1.643g of 6FDA, and 1.200g of TFMB.

[0039] (2) Preparation of dianhydride solution. Add 50 mL of N,N-dimethylacetamide (DMAc) to a 250 mL three-necked flask and cool to 0 °C in an ice-water bath. Add PTCDA and 6 FDA in the above proportions and stir magnetically at 0 °C for 30 min to fully dissolve the dianhydride monomer, resulting in a deep red homogeneous solution.

[0040] (3) Preparation of diamine solution. Take another 75 mL beaker, add TFMB monomer in an amount equal to the total amount of dianhydride monomer, then add 50 mL of DMAc solvent, and stir for 20 min at 0 °C to obtain a colorless and transparent diamine solution.

[0041] (4) Polymerization reaction. To avoid problems such as uneven polymerization and aggravated side reactions caused by excessively high local monomer concentration, the 0℃ ice-water bath environment was maintained throughout the process. The diamine transparent solution obtained in step (3) was slowly added dropwise to the dianhydride dark red solution obtained in step (2), and the magnetic stirring speed was controlled to be no less than 800 rpm. The stirring reaction was continued for 60 min, and finally a uniform and stable dark red PAA polymer emulsion was obtained.

[0042] (5) Product precipitation and purification. After the reaction was completed, the obtained PAA emulsion was slowly added dropwise to 300 mL of deionized water to achieve phase separation and precipitation of the polymer, resulting in red spherical solid particles. The solid product was collected by centrifugation at 8000 rpm for 10 min, and washed repeatedly with deionized water 2-3 times to thoroughly remove the unreacted monomers and organic solvents remaining in the system. Finally, the product was dried at room temperature in a vacuum drying oven to obtain red polyamic acid precursor particles, named PAA1.

[0043] (6) Preparation of intrinsic red polyimide nanoparticles by microfluidic method. The obtained PAA1 microparticles were redissolved in DMAc to prepare a 6 wt% red polyamic acid solution as the microfluidic dispersion phase. Silicone oil containing 2 wt% Span80 was used as the continuous phase. A flow-focusing microfluidic chip (channel size 100 μm) was used to control the flow rate of the dispersed phase at 2 mL / h and the flow rate of the continuous phase at 20 mL / h to generate monodisperse red polyamic acid emulsion droplets.

[0044] After solvent displacement of the emulsion droplets: the solvent diffuses out of the emulsion droplets through extraction, and the red modified PAA is solidified in situ into spherical nanoparticles. The solidified spherical nanoparticles are collected and subjected to thermal imidization under vacuum conditions using a stepped heating program: the temperature is increased stepwise in vacuum stages of 100℃, 150℃, 200℃, 250℃, and 300℃, with each temperature stage held for 1 hour, to obtain intrinsic red polyimide nanoparticles, named PI1.

[0045] Example 2 The preparation of intrinsic red polyimide nanoparticles with a PTCDA molar ratio of 30% is detailed below: The method is the same as in Example 1, except that the molar percentage of PTCDA in the mixed dianhydride is 30%, corresponding to the weighing of 0.472g of PTCDA, 1.333g of 6FDA, and 1.200g of TFMB.

[0046] After microfluidic emulsion droplet generation, solvent displacement curing, and step-heat thermal imidization treatment, intrinsic red polyimide nanoparticles were obtained and named PI2.

[0047] Example 3 The preparation of intrinsic red polyimide nanoparticles with a PTCDA molar ratio of 50% is detailed below: The method is the same as in Example 1, except that the molar ratio of PTCDA in the mixed dianhydride is 50%, corresponding to the weighing of 0.787g of PTCDA, 1.000g of 6FDA, and 1.200g of TFMB.

[0048] After microfluidic emulsion droplet generation, solvent displacement curing, and step-heat thermal imidization treatment, intrinsic red polyimide nanoparticles were obtained and named PI3.

[0049] Comparative Example Without the addition of PTCDA, TFMB and 6FDA were used as raw materials to prepare polyimide according to the method of Example 1.

[0050] Performance tests are as follows: Particle size and morphology analysis were performed on PI1 from Example 1, such as... Figure 1 and Figure 2 As shown, the results indicate that the nanoparticles are regularly spherical with a narrow particle size distribution and highly uniform size, belonging to a monodisperse system. Uniform particle size ensures consistent display contrast, while the regular spherical shape reduces light scattering and guarantees consistent forces in the electric field. FTIR tests were performed on the polyimide nanoparticles obtained in Examples 1, 2, and 3. A value of 1780 cm⁻¹ was observed in all of the spectra. -1 (C=O asymmetric stretching vibration), 1720cm -1 (C=O symmetric stretching vibration) and 1380cm -1 The characteristic absorption peak of (CN stretching vibration) confirms the formation of the polyimide structure. The FTIR test results of PAA2 and PI2 in Example 2 are as follows: Figure 3 As shown.

[0051] Color coordinate tests were performed on Examples 1, 2, 3 and the comparative example, and the results are shown in Table 1.

[0052] Table 1 Chromaticity coordinates (CIE1931 x, y) for each embodiment As shown in Table 1, the x and y values ​​gradually increase and then stabilize as the PTCDA doping ratio increases, indicating that the red hue gradually deepens.

[0053] Figure 4The Zeta potentials of PI1, PI2, and PI3 in nonpolar dispersion media were compared. PI2 exhibited a significantly higher absolute Zeta potential of 239.12 mV than PI1 and PI3, indicating the highest surface charge density, strongest electrostatic repulsion between particles, and excellent dispersion stability in the electrophoretic medium. This high Zeta potential directly corresponds to a high charge-to-mass ratio, enabling PI2 to achieve sufficient electrophoretic mobility at lower electric field strengths, providing a crucial foundation for achieving low-voltage drive (<30V) and rapid electric field response. The relatively low absolute Zeta potential of PI3 may be due to the excessively high PTCDA content altering the particle surface properties and affecting the effective adsorption of the charge control agent. This also indirectly confirms the existence of an optimization window for the PTCDA doping ratio.

[0054] PI2 nanoparticles were dispersed in Isopar G (isoalkane solvent G), and a charge control agent (polyisobutylene succinimide compound) was added to prepare a 10 wt% red electrophoretic ink. Titanium dioxide nanoparticles were also dispersed in Isopar G (isoalkane solvent G), and a charge control agent (polyisobutylene succinimide compound) was added to prepare a 10 wt% white electrophoretic ink. The red and white electrophoretic inks were mixed to obtain a red-white bicolor electrophoretic ink. The resulting red-white bicolor electrophoretic ink was encapsulated in an ITO electrode test box, and a DC voltage (±15V~40V) was applied. The electrophoretic ink migration response time of the PI2 nanoparticles was recorded, as shown in Table 2.

[0055] Table 2 Response time of electrophoretic ink formulated with PI2 nanoparticles Test results show that the red electrophoretic particles obtained by this invention have a fast electric field response (response time <300ms). Under a driving voltage of ±30V, the device exhibits good electrical response characteristics, with a response time of 227ms for switching from the red state to the white state and 259ms for switching from the white state to the red state, demonstrating excellent bistable display performance.

[0056] Based on the response time data (Table 2), the optimal response is achieved at ±30V: 227ms from red to white and 259ms from white to red, both <300ms. As the voltage is further increased to 35V and 40V, the response time fluctuates slightly (e.g., 264ms, 271ms, etc.), indicating that ±30V is the optimal driving voltage window for the electrophoresis device of this invention.

[0057] In summary, the intrinsic red polyimide nanoparticles prepared by microfluidic technology in this invention exhibit outstanding performance in three key technical indicators: intrinsic color stability, high charge-to-mass ratio in non-polar media, and rapid low-voltage electrophoretic response. This solves the technical problems of traditional color electrophoretic particles, such as easy color fading, low charge-to-mass ratio, high driving voltage, and slow response, and has significant industrial application value in the field of color electronic paper displays.

[0058] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A method for preparing intrinsically red polyimide nanoparticles, characterized in that, include: PTCDA and 6FDA were dissolved in a solvent to obtain a dianhydride solution. TFMB was dissolved in a solvent to obtain a diamine solution. The dianhydride solution and the diamine solution were mixed and reacted to obtain a mixed solution containing red modified PAA. A mixed solution containing red modified PAA was added dropwise to water and then centrifuged to obtain red modified PAA microparticles. The red modified PAA microparticles were then dissolved in a solvent to obtain a red modified PAA solution. A red modified PAA solution was used as the dispersed phase, and an oily solvent containing a surfactant was used as the continuous phase. The solution was passed through a microfluidic chip to generate emulsion droplets. The emulsion droplets were then dropped into water and centrifuged to obtain red modified PAA nanoparticles. The red modified PAA nanoparticles were subjected to step-heat thermal imidization to obtain intrinsic red polyimide nanoparticles. The solvent in the red modified PAA solution is immiscible with oily solvents, while the solvent in the red modified PAA solution is miscible with water. Oily solvents are unsuitable solvents for red modified PAA.

2. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, The red modified PAA solution contains 5-7 wt% red modified PAA, and the oily solvent containing surfactant contains 1-3 wt% surfactant.

3. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, The total amount of PTCDA and 6FDA is in a 1:1 ratio with the amount of TFMB.

4. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, When the mixed solution containing red modified PAA is dropped into water, the red modified PAA molecular chains collapse and aggregate in the desolvated environment after the solvent is replaced by water, forming red modified PAA microparticles.

5. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, The microfluidic chip has a channel size of 50~500μm, a dispersed phase flow rate of 0.5~10mL / h, and a continuous phase flow rate of 5~100mL / h.

6. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, When the emulsion droplets are dropped back into water, the oily solvent separates into layers with the water. The solvent in the red modified PAA solution diffuses out of the emulsion droplets and is extracted and replaced by water. The red modified PAA molecular chains collapse and aggregate in the desolvated environment, forming red modified PAA nanoparticles.

7. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, The specific method for the stepped heating thermal imidization is as follows: under vacuum conditions, the temperature is gradually increased in stages of 100℃, 150℃, 200℃, 250℃, and 300℃, and each temperature stage is held for 1 hour.

8. The method for preparing intrinsic red polyimide nanoparticles according to claim 1, characterized in that, The reaction between the dianhydride solution and the diamine solution is a condensation reaction. PTCDA and 6FDA randomly undergo condensation reaction with TFMB to obtain red modified PAA. The perylene core of PTCDA is covalently embedded in the main chain of red modified PAA as a red chromophore.

9. Intrinsic red polyimide nanoparticles prepared by the preparation method according to any one of claims 1 to 8.

10. An electrophoretic ink comprising the intrinsic red polyimide nanoparticles as described in claim 9.